Growth rates in thoroughbred foals - Mohd Jelan, Zainal Aznam; Jeffcott, Leo B.; Lundeheim, Nils; Osborne, M. (Hippiatrika Verlag, 1996)
Data of 798 Thoroughbred horses foaled in 1988 to 1992 in Co. Kildare, Ireland were examined in a study to provide detailed information on a range of parameters on normal growth and development from birth to 20 months of age (onset of training). Based on average body weight gain, the pattern of growth in Thoroughbred horses destined for flat racing could be divided into four phases; each was characterized by markedly different growth rate. However, this pattern was not observed for withers height where the rate gradually declined following an initial rapid growth in the first 6 months of age. Differences of body weight and height at the withers between normal and DOD-affected horses were not significant (P>0.05). These investigations appear to indicate that the body weight and withers height and their rates of growth were not critical in causing developmental skeletal problems. This is contrary to most other studies which suggested that the rate of growth is related to many developmental skeletal abnormalities in young Thoroughbred horses.